2016
DOI: 10.1016/j.amepre.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Rise of Electronic Nicotine Delivery Systems Using Search Query Surveillance

Abstract: Introduction Public perceptions of electronic nicotine delivery systems (ENDS) remain poorly understood because surveys are too costly to regularly implement and when implemented there are large delays between data collection and dissemination. Search query surveillance has bridged some of these gaps. Herein, ENDS’ popularity in the U.S. is reassessed using Google searches. Methods ENDS searches originating in the U.S. from January 2009 through January 2015 were disaggregated by terms focused on e-cigarette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 55 publications
(43 reference statements)
3
71
0
Order By: Relevance
“…Similar to recent research of Google search terms in the United States, 5 we found that derivations of "vape" increased in popularity between 2013-2015, suggesting that this is also an emerging native term for ENDS among US adult current and former smokers. BecomeAnEX users seldom employed ENDS brand names or researcher-generated Category combines multiple keywords, as specified below: ecig: e-cig*, e cig*, ecig*, electronic cig* vape: vape*, vapour*, vapor* blu: blu, blucig, blu cig* e-liquid: e-liquid*, eliquid*, e liquid* e-juice: e-juice*, ejuice*, e juice* e-pipe: e-pipe*, epipe*, e pipe* e-nicotine: e-nicotine*, enicotine*, e nicotine*, electronic nicotine e-cigar: e-cigar, ecigar, e cigar cigalike: cig-alike*, cig-a-like*, cigalike* e-hookah: e-hookah*, ehookah*, e hookah* e-sisha: e-sisha*, esisha*, e sisha* e-vape: e-vape*, evape*, e vape* terms such as "electronic nicotine device."…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar to recent research of Google search terms in the United States, 5 we found that derivations of "vape" increased in popularity between 2013-2015, suggesting that this is also an emerging native term for ENDS among US adult current and former smokers. BecomeAnEX users seldom employed ENDS brand names or researcher-generated Category combines multiple keywords, as specified below: ecig: e-cig*, e cig*, ecig*, electronic cig* vape: vape*, vapour*, vapor* blu: blu, blucig, blu cig* e-liquid: e-liquid*, eliquid*, e liquid* e-juice: e-juice*, ejuice*, e juice* e-pipe: e-pipe*, epipe*, e pipe* e-nicotine: e-nicotine*, enicotine*, e nicotine*, electronic nicotine e-cigar: e-cigar, ecigar, e cigar cigalike: cig-alike*, cig-a-like*, cigalike* e-hookah: e-hookah*, ehookah*, e hookah* e-sisha: e-sisha*, esisha*, e sisha* e-vape: e-vape*, evape*, e vape* terms such as "electronic nicotine device."…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, recent research in the United States using Google Trends suggests that ENDS terms vary by location, with derivations of "vape" more common in coastal regions than in the rest of the United States. 5 The variety of terms for the diverse ENDS product class has motivated discussion of a need for measures development, [6][7][8] but there is little published methods development work.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support related research regarding the terms people use when searching for e-cigarettes online. 6 …”
Section: Discussionmentioning
confidence: 99%
“…These findings support related research regarding the terms people use when searching for e-cigarettes online. 6 Social media research on e-cigarettes has focused on using data from Twitter, with recent studies examining perception, 9 awareness 30 31 and advertising. 10 14 While sites such as Twitter were created before the ubiquitous use of smartphones, Instagram originated as a smartphone app, with features that rely on mobile devices that can take high-quality photos and have fast internet connections; when combined with vaping activities (eg, cloud chasing) that are best suited for real-time capture and sharing, it makes Instagram an ideal platform for ecigarette users and provides ample data for researchers to explore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation